Comparative effectiveness of transverse oscillatory pressure and cervical traction in the management of cervical radiculopathy: A randomized controlled study - Adesola Ojo Ojoawo; Ayodele Damilare Olabode (World Scientific Publishing, 2018)
Background: Radiating neck pain is one of the major symptoms of cervical radiculopathy (CR). Objective: This study compared the effects of cervical traction (CT) and transverse oscillatory pressure (TOP) in management of CR. Methods: Seventy-five participants with unilateral radiating neck pain were randomly allocated into three groups, 25 (14 males, 11 females) for CT, 25 (15 males and 10 females) for TOP and 25 (11 males and 14 females) control (Cnt) group. All participants received massage, cryotherapy and active exercises three times in a week for six weeks. CT was administered to CT group, TOP to TOP group while the third group served as control. Pain intensity (PI) and neck functional disability (NFD) were assessed pretreatment, 3rd and 6th week of intervention. Data were analyzed using descriptive and inferential statistics. Results: There was a significant reduction in PI and NFD between pretreatment and 6th week in all the groups (p<0.05). The effect size of PI (F=7.533, p<0.001) and disability index (F=37.888, p<0.001) in CT group were significantly lower than that of TOP group at 3rd week. PI of TOP was significantly (p<0.05) lower than that of CT and Cnt groups at the 6th week. Conclusion: TOP reduces the PI and disability of patients with CR faster compared to CT.